UJI VALIDITAS DAN RELIABILITAS SCALES FOR OUTCOME IN PARKINSONS DISEASEAUTONOMIC SCOPAAUT UNTUK MENILAI GANGGUAN FUNGSI OTONOM PADA PENYAKIT PARKINSON - Basli*, Freddy Sitorus**, Eva Dewati**, Herqutanto*** (Neurona Majalah Kedokteran Neuro Sains, 2011)
INTRODUCTION PARKINSONS DISEASE IS THE MOST FREQUENT TYPE OF PARKINSONISM AND THE SECOND MOST FREQUENT DISEASE AFTER ALZHEIMERS DEMENTIA AUTONOMIC DYSFUNCTION IN PARKINSONS DISEASE HAS THE SIGNS AND SYMPTOMS ASSOCIATED WITH GASTROINTESTINAL URINARY SEXUAL CARDIOVASCULAR THERMOREGULATION AND PUPILLOMOTOR ABNORMALITIES